Gaps in evidence for the use of medically authorized cannabis: Ontario and Alberta, Canada - Cerina Lee; Jessica M. Round; Scott Klarenbach; John G. Hanlon; Elaine Hyshka; Jason R. B. Dyck; Dean T. Eurich (BMC, 2021)
Abstract Background With legal access to medical cannabis in Canada since 2001, there is a need to fully characterize its use at both the individual and population levels. We draw on data from Canada's largest cohort study of medical cannabis to identify the primary reasons for medical cannabis authorization in Canada from 2014 to 2019 in two major provinces: Alberta (AB) and Ontario (ON), and review the extent that evidence supports each indication. Methods Self-reported baseline assessments were collected from adult patients in ON (n = 61,835) and AB (n = 3410) who were authorized medical cannabis. At baseline, sociodemographic, primary medical information, and validated clinical questionnaires were completed by patients as part of an individual assessment. Patients' reasons for seeking medical cannabis were compared to published reviews and guidelines to assess the level of evidence supporting medical cannabis use for each condition. Results Medical cannabis use in both AB and ON was similar in both demographic and reason for authorization. The most common reasons for medical cannabis authorization were: (1) pain (AB = 77%, ON = 76%) primarily due to chronic musculoskeletal, arthritic, and neuropathic pain, (2) mental health concerns (AB = 32.9%, ON = 38.7%) due to anxiety and depression, and (3) sleep problems (AB = 28%, ON = 25%). More than 50 other conditions were identified as reasons for obtaining authorization. Conclusion In both AB and ON, the majority of reasons for medical cannabis authorization are not substantiated by clinical evidence to fully support its efficacy for long-term use. Ongoing epidemiological studies on medical cannabis on these treatments are warranted to fully outline its treatment benefits or risks.